Understanding Issues Affecting Students’ Commitment to Online Discussion Forums in Undergraduate Courses - Aderibigbe, Semiyu Adejare; Dias, Jacqueline Maria; Abraham, Mini Sara (International Journal of Interactive Mobile Technologies (iJIM), 2021)
This study explored students’ commitment and factors impacting their commitment to the online discussion forums that complement teaching and learning in two undergraduate courses. Using a combination of quantitative and qualitative strategies, we collected and analyzed data to address our research questions. The findings indicate that students are committed to online discussion forums in this study, which seemed to be impacted by students’ technological skills and exciting topics. Even so, a few students were not as committed as they would have liked because the platform was new, and they needed time to adapt to the learning platform. That said, our findings reveal that students’ commitment to and engagement in the online discussion forum can be fostered with faculty support, exciting topics, and time to understand the new learning terrain.